Rosaceae Fruit Development, Ripening and Post-harvest: An Epigenetic Perspective - Farinati, Silvia; Rasori, Angela; Varotto, Serena; Bonghi, Claudio (Frontiers in Plant Science, 2017)
Rosaceae is a family with an extraordinary spectrum of fruit types, including fleshy peach, apple, and strawberry that provide unique contributions to a healthy diet for consumers, and represent an excellent model for studying fruit patterning and development. In recent years, many efforts have been made to unravel regulatory mechanism underlying the hormonal, transcriptomic, proteomic and metabolomic changes occurring during Rosaceae fruit development. More recently, several studies on fleshy (tomato) and dry (Arabidopsis) fruit model have contributed to a better understanding of epigenetic mechanisms underlying important heritable crop traits, such as ripening and stress response. In this context and summing up the results obtained so far, this review aims to collect the available information on epigenetic mechanisms that may provide an additional level in gene transcription regulation, thus influencing and driving the entire Rosaceae fruit developmental process. The whole body of information suggests that Rosaceae fruit could become also a model for studying the epigenetic basis of economically important phenotypes, allowing for their more efficient exploitation in plant breeding.